2006
DOI: 10.1038/sj.ejcn.1602564
|View full text |Cite
|
Sign up to set email alerts
|

Effects of meals with high soluble fibre, high amylose barley variant on glucose, insulin, satiety and thermic effect of food in healthy lean women

Abstract: Objective: To examine the effect of barley flour (barley cultivar, Hordeum Vulgare var Himalaya 292) incorporated into breakfast and lunch compared with otherwise identical meals containing white wheat flour on the thermic effect of food (TEF), subsequent food intake and metabolic parameters. Design: Randomized single blinded crossover study. Setting: Outpatient setting. Subjects and methods: Fourteen healthy women consumed a test breakfast at 0700 h. Energy expenditure, respiratory quotient (RQ), appetite rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(47 citation statements)
references
References 40 publications
5
40
2
Order By: Relevance
“…This concurs with some rodent data that suggest that food intake is increased to compensate for the diluted energy density of a high RS diet (Zhou, Martin et al 2008). Human data from RS studies (Keogh, Lau et al 2007) and other nutritional interventions (Zaveri and Drummond 2009) add credence to the idea that both rats and humans might increase total food intake to compensate for a diet of lower energy density.…”
Section: Introductionmentioning
confidence: 92%
“…This concurs with some rodent data that suggest that food intake is increased to compensate for the diluted energy density of a high RS diet (Zhou, Martin et al 2008). Human data from RS studies (Keogh, Lau et al 2007) and other nutritional interventions (Zaveri and Drummond 2009) add credence to the idea that both rats and humans might increase total food intake to compensate for a diet of lower energy density.…”
Section: Introductionmentioning
confidence: 92%
“…Metabolic rate was measured by indirect calorimetry in the fasting state and postprandially for 5 h. Results showed that the replacement of digestible starch by RS in a single meal lowered DIT, however, the ingestion of lactulose resulted in a substantial rise in DIT which was related to its fermentation [34]. A more recent crossover study by Keogh and coworkers [35] examined the effect of barley flour, high in soluble fiber and amylose, incorporated into breakfast and lunch compared with otherwise identical meals containing white wheat flour on the thermic effect of food. Fourteen healthy women consumed a test breakfast at 7:00 and a test lunch at 13:30.…”
Section: Starches Obesity and Factors Of The Metabolic Syndromementioning
confidence: 99%
“…However, despite improved satiety, test products high in dietary fibre did not result in altered energy intake in other studies (Kristensen et al, 2010;Schroeder et al, 2009;Kim et al, 2006;Berti et al, 2005;Delargy et al, 1997;Levine et al, 1989). One study (Keogh et al, 2007) even measured a self-reported increase in energy intake following the high-fibre barley diet. The inconsistent relationship between perceived satiety and subsequent energy intake may relate to the timing of the test meals, which varies between 75-270 min after test food intake.…”
Section: Control: Refined Wheat Bread (Low-fiber)mentioning
confidence: 98%